(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The current research aims to identify the level of positive thinking among university students at the University of Kirkuk and to know the differences in positive thinking according to the gender variable (male - female) and specialization (scientific - human). The current research community consists of university students at the University of Kirkuk for the academic year 2021-2022 and a sample was formed. The basic research consisted of (300) male and female students (150) males and (150) females, and the number of faculties was (16) colleges (4) Humanities colleges and (4) scientific colleges. To achieve the research objectives, the researcher prepared a scale tool to measure positive thinking, which consists of four dimensions: (positive acceptance, acceptance of personal responsibility, tolerance and cooperation, and positive expectations), as the scale consists of (39) items. The apparent validity of the scale was verified by presenting its paragraphs to a group of arbitrators, as well as extracting the discrimination coefficient and correlation coefficient for the scale’s paragraphs, and thus the scale became in its final form consisting of (37) items, and the scale’s stability was calculated by re-testing, and it amounted to (0.85).